Emerging Perspectives on Dipeptide Repeat Proteins in C9ORF72 ALS/FTD - Schmitz, Alexander; Pinheiro Marques, João; Oertig, Irina; Maharjan, Niran; Saxena, Smita (Frontiers in Cellular Neuroscience, 2021)
The most common genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) is a hexanucleotide expansion in the chromosome 9 open reading frame 72 gene (C9ORF72). This hexanucleotide expansion consists of GGGGCC (G4C2) repeats that have been implicated to lead to three main modes of disease pathology: loss of function of the C9ORF72 protein, the generation of RNA foci, and the production of dipeptide repeat proteins (DPRs) through repeat-associated non-AUG (RAN) translation. Five different DPRs are currently known to be formed: glycine–alanine (GA) and glycine–arginine (GR) from the sense strand, proline–alanine (PA), and proline–arginine (PR) from the antisense strand, and glycine–proline (GP) from both strands. The exact contribution of each DPR to disease pathology is currently under intense scrutiny and is still poorly understood. However, recent advances in both neuropathological and cellular studies have provided us with clues enabling us to better understand the effect of individual DPRs on disease pathogenesis. In this review, we compile the current knowledge of specific DPR involvement on disease development and highlight recent advances, such as the impact of arginine-rich DPRs on nucleolar protein quality control, the correlation of poly-GR with neurodegeneration, and the possible involvement of chimeric DPR species. Further, we discuss recent findings regarding the mechanisms of RAN translation, its modulators, and other promising therapeutic options.